Public Support for the Euro and Trust in the ECB. The First Two Decades of the Common Currency - Felix Roth; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2019)
This chapter examines the evolution of public support for the euro and public trust in the European Central Bank (ECB) during the new currency's first two decades. Using a unique set of opinion poll data that is not available for any other currency, we find that a majority of citizens in every member country of the euro area (EA) support the euro. The economic crisis in the EA following the Great Recession and the euro crisis led to a slight decline in public support for the euro but a sharp fall in trust in the ECB. The recent economic recovery has strengthened support for the euro as well as trust in the ECB. We suggest that support for the euro as a medium of exchange was not strongly affected by the crisis, while trust in the ECB, as the framer of monetary policy, was measurably weakened by the crisis. Our econometric work demonstrates that unemployment is a key driver of support for the euro and its governance. Given these developments, we discuss whether the present levels of support for the euro equip the currency to weather populist challenges in the coming decade.
Keywords: E42; E52; E58; F33; F45; 330; Euro; public support; trust; unemployment; optimum currency area; monetary union; ECB; EU